2016
DOI: 10.1149/2.0191701jes
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Ethylene Carbonate-Free Electrolyte Making for Li-Ion Cells

Abstract: Li [Ni 0.42 Mn 0.42 Co 0.16 ]O 2 (NMC442)/graphite pouch cells demonstrate superb performance at high voltage when ethylene carbonate (EC)-free electrolytes, using a solvent mixture that is >95% ethyl methyl carbonate (EMC) and between 2 and 5% of an "enabler", are used. The "enablers", required to passivate graphite during formation, can be vinylene carbonate (VC), methylene-ethylene carbonate (MEC), fluoroethylene carbonate (FEC) or difluoro ethylene carbonate (DiFEC), among others. In order to optimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 37 publications
6
119
0
Order By: Relevance
“…10,17 In freshly formed cells the presence of these products indicates the existence of Li-alkoxides, likely formed from the reduction of EMC at an un-passivated anode. 8,10,17 Li-alkoxide formation and subsequent reaction with linear carbonate are shown in Equation 1 and Equation 2, respectively. The presence of transesterification products later in life was hypothesized to originate from the passivation of dissolved transition metals upon deposition at the negative electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17 In freshly formed cells the presence of these products indicates the existence of Li-alkoxides, likely formed from the reduction of EMC at an un-passivated anode. 8,10,17 Li-alkoxide formation and subsequent reaction with linear carbonate are shown in Equation 1 and Equation 2, respectively. The presence of transesterification products later in life was hypothesized to originate from the passivation of dissolved transition metals upon deposition at the negative electrode.…”
Section: Resultsmentioning
confidence: 99%
“…5 Aged lithium-ion cells with many cycles or after testing in extreme conditions show dramatic electrolyte changes. [6][7][8] Recorded electrolyte changes include oxidation at the positive electrode, 7,9 reduction at the negative electrode, 7,9 dimerization of ethylene carbonate (EC) and linear carbonates, 8 transesterification of the linear carbonates, 10 LiPF 6 break down and subsequent reactions, 7,[11][12][13] and consumption of active Li and electrolyte in solid electrolyte interphase (SEI) formation. 7,14 These reactions may be paired with electrode transformations later in cell life including changes to the positive electrode surface structure from layered to spinel 1,15 and transition metal dissolution from the positive electrode followed by deposition on the negative electrode.…”
mentioning
confidence: 99%
“…Some of these strategies will be used in the work here. For example, Petibon et al and Ma et al 13,14 showed that ethylene carbonate (EC)-free electrolytes, like 1M LiPF 6 in 95% ethyl methyl carbonate with 5% fluoroethylene carbonate was very effective in allowing NMC/graphite cells to operate to 4.4 V. EC-free electrolytes will be explored in this preliminary work.Electrolyte additives like pyridine boron trifluoride (PBF) and pyridine phosphorus pentafluoride (PPF) have been reported to provide * Electrochemical Society Fellow.z E-mail: jeff.dahn@dal.ca; huangl@xmu.edu.cn better capacity retention during high-voltage and high temperature cycling of NMC/graphite cells. 15,16 Their use will be explored in this preliminary work.…”
mentioning
confidence: 99%
“…Recently, it was found that EC-free electrolyte using only ethyl methyl carbonate as the solvent can enhance high voltage operation and lifetime of NMC442/graphite pouch cells compared to EC-based electrolyte. [30][31][32] However, only a salt concentration of 1 M LiPF 6 in this novel electrolyte was investigated.…”
mentioning
confidence: 99%